Design an Android education program using video tutorials in Bangla - Al Hasan, Syed Rakib; Dores, Bellonal Lillian (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2010.